Nghiên cứu ảnh hưởng của nhiệt độ, tỷ lệ mol Ce/Fe đến sự hình thành pha oxit hỗn hợp CeO2-Fe2O3. - Nhiệm, Đào Ngọc; Dũng, Đoàn Trung; Văn, Nguyễn Đức; Chức, Phạm Ngọc; Hà Chi, Nguyễn Thị (Vietnam Journal of Chemistry, 2016)
The preparation of CeO2-Fe2O3 mixed oxides by combustion method using cerium(IV) nitrate, iron(III) nitrate and polyvinyl alcohol (PVA) was described in this paper. Effects of preparative parameters namely, calcination temperature, Ce/Fe molar ratio on the phase formation of CeO2–Fe2O3 mixed oxides were investigated. The prepared CeO2–Fe2O3 mixed oxides powders were characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and specific surface area analysis from N2 adsorption data at 77 K by Brunaure-Emmet-Teller (BET) method. Samples synthesized under optimal conditions has an average crystalline size < 50 nm with large specific area of 68.9 m2/g. Keywords. CeO2–Fe2O3 mixed oxide, cerium(IV) nitrate, iron(III) nitrate, polyvinyl alcohol, combustion method.